A simulation and optimization based method for calibrating agent-based emergency department models under data scarcity. (January 2017) - Liu, Zhengchun; Rexachs, Dolores; Epelde, Francisco; Luque, Emilio
Highlights: A method to calibrate an emergency department model with incomplete data. Simulation-based optimization for model parameter calibration. An accurate emergency department simulator. Abstract: To tackle the problem of efficiently managing increasingly complex systems, simulation models have been widely used. This is because simulation is safer, less expensive, and faster than field implementation and experimenting. To achieve high fidelity and credibility in conducting prediction and exploration of the actual system with simulation models, a rigorous calibration and validation procedure should firstly be applied. However, one of the key issues in calibration is the acquisition of valid source information from the target system. The aim of this study is to develop a systematic method to automatically calibrate a general emergency department model with incomplete data. The simulation-based optimization was used to search for the best value of model parameters. Then we present a case study to particularly demonstrate the way to calibrate an agent-based model of an emergency department with real data scarcity. The case study indicates that the proposed method appears to be capable of properly calibrating and validating the simulation model with incomplete data.